2010
DOI: 10.1038/nphys1499
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in one-atomic-layer metal films grown on Si(111)

Abstract: The two-dimensional (2D) superconducting state is a fragile state of matter susceptible to quantum phase fluctuations. Although superconductivity has been observed in ultrathin metal films down to a few layers 1-10 , it is still not known whether a single layer of ordered metal atoms, which represents the ultimate 2D limit of a crystalline film, could be superconducting. Here we report scanning tunnelling microscopy measurements on single atomic layers of Pb and In grown epitaxially on Si(111) substrate, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
367
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 505 publications
(400 citation statements)
references
References 29 publications
(38 reference statements)
20
367
3
2
Order By: Relevance
“…Robust superconductivity has already been reported in some atomically thin conventional superconductors [32][33][34] . Our investigations reveal that this phenomenon could also be observed in high-T c superconductor.…”
Section: Discussionmentioning
confidence: 87%
“…Robust superconductivity has already been reported in some atomically thin conventional superconductors [32][33][34] . Our investigations reveal that this phenomenon could also be observed in high-T c superconductor.…”
Section: Discussionmentioning
confidence: 87%
“…Previous scanning tunnelling spectroscopy (STS) studies have shown that the SIC phase is superconducting with T C_SIC = ∼1.8 K (ref. 17) and the 2D Pb islands have a T C around 6 K (ref. 18), although the actual T C value also depends on the lateral size as well as its thickness 19 .…”
mentioning
confidence: 99%
“…with the earlier work on superconducting oxides interfaces [3][4][5][6] , demonstrates that interface between two different materials provide not only a rich system for studying two-dimensional (2D) superconductivity, but also a potential pathway to high-T c superconductivity [7][8][9][10][11][12] .…”
mentioning
confidence: 80%